Vector Control Applied to Mitigate the Electromagnetic Torque Ripple in Doubly Fed Induction Generator - Desantana, Marcelo PATRICIO (2021)
This paper proposes a novel Vector Control topology for stator current harmonic mitigation, due to the grid voltage harmonic content, focusing on mitigating the torque undulations in the Doubly Fed Induction Generator. The Proposed Controller referred here as to HVC - Harmonic Vector Control, is capable of mitigating any desired current harmonic. For sake of clarity, the HVC has been tested for fifth, seventh, eleventh and thirteenth current harmonics since they are the most common harmonics in the grid voltage. In addition, the proposed control is robust to the machine's parameters variation, to the grid frequency oscillation and does not require a harmonic filter to estimate the harmonic content present in the stator current due to the power grid, which are the main disadvantages found in literature for the existing controllers. Firstly, the control topology is described and explained in detail. Next, simulation and experimental data are shown and compared to prove the suitability, efficacy and robustness of the proposed control. In the cases studied, the steady state error of the proposed controller is close to zero. Furthermore, the HVC can be used as a harmonic filter in DFIG and the harmonics can be chosen according to the application requirements.